COMPARATIVE ANALYSIS OF EVOLUTION AND HISTORY OF THE IDEOLOGY OF ASCETICISM IN CHRISTIANITY AND ISLAM - Khudayberganova Gulnora Nasirovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
One of the common features of all religions in the world is ascetic (Greek askesis (in Christianity) - the movement of the human will on the way to achieve divine grace), ar. zuhd-alzhd – not to incline the heart to the world) is the existence of views and practices in one form or another. But this situation does not require that the ascetic processes in religions are exactly the same, but the ascetic state, formed separately in each religion, acquires its own characteristics. This can be observed as a unique phenomenon in monotheistic (Greek monos-theos - monotheistic) and polytheistic (Greek poly-theos - polytheistic) religions and religious-philosophical teachings. Today, the basis of ascetic views in Christianity and Islam, which are among the world religions, is of great importance due to the presence of a number of common and different aspects based on the reliance on sacred sources, development stages and evolution, institutionalization processes, and their place in social life.